Brazil's second chance : en route toward the first world - Gordon, Lincoln (Brookings Institution Press, 2001)
"Brazilians have always envisioned for their nation a future of greatness on the world stage. Now, after two centuries of independent statehood, Brazil appears to be making great strides toward first world status. Since the 1950s, this largest of the South American countries has evolved from a patrimonial society - based mainly on the cultivation and export of sugar and coffee - toward a modernized industrialized and service economy with effective democratic governance." "In this new work, a political economist and former U.S. ambassador to Brazil examines the social, political, and economic history of the country since the 1950s and discusses whether Brazil is ready to assume a place among first world nations. Drawing on his own long-term professional and personal relationship with Brazil, Lincoln Gordon evaluates the country's future prospects through the lens of history and policy. He traces Brazil's development efforts over the past fifty years, highlighting significant missteps as well as successes. Gordon identifies four key policy challenges that Brazil must address: consolidation of macroeconomic stability, poverty reduction, active engagement in the global economy, and political reform."--Jacket